2018
DOI: 10.4103/ijn.ijn_297_16
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid proximal tubulopathy and amyloid casts: An unusual finding in multiple myeloma

Abstract: Patients with multiple myeloma (MM) often develop renal manifestations. The majority of cases present as cast nephropathy, amyloid light-chain (AL) amyloidosis, and monoclonal immunoglobulin deposition disease. AL amyloidosis usually involves the glomeruli, blood vessels, and interstitium. It is extremely uncommon to find isolated intratubular deposition of AL amyloid. Our patient presented with rapid worsening of renal function due to isolated intratubular deposition of AL amyloid, where the biopsy revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This hypothesis is in agreement with previous studies done by Shirahama and Cohen9 suggesting that proteolytic enzyme processing of immunoglobulin light chains within the lysosomes is central to amyloid fibril formation. Recently, Kurien and Fernando10 from India and Iliuta et al 11 from Canada have reported a similar case of amyloid cast with amyloid proximal tubulopathy. Proximal tubulopathy was not present in our case.…”
Section: Discussionmentioning
confidence: 86%
“…This hypothesis is in agreement with previous studies done by Shirahama and Cohen9 suggesting that proteolytic enzyme processing of immunoglobulin light chains within the lysosomes is central to amyloid fibril formation. Recently, Kurien and Fernando10 from India and Iliuta et al 11 from Canada have reported a similar case of amyloid cast with amyloid proximal tubulopathy. Proximal tubulopathy was not present in our case.…”
Section: Discussionmentioning
confidence: 86%
“… Friman C [ 10 ] 1970 1 a Distal Laminated ND No Yes in tumour, No in other organs Limas C [ 11 ] 1973 15 a convoluted tubules, loops of Henle, etc. Rimmed ND PTC cytoplasm in 3 cases No c Melato M [ 12 ] 1980 4 a ND Rimmed Laminated Homogeneous ND No No El-Zoghby Z [ 13 ] 2007 1 b ND Rimmed λ PTC cytoplasm Yes in BM and joint Nasr SH [ 14 ] 2008 1 b ND Rimmed λ No ND Sethi S [ 15 ] 2009 1 b ND Rimmed λ No No in BM Sharma A [ 16 ] 2014 1 b ND Rimmed λ No No in BM Kato H [ 6 ] 2015 1 b Distal Rimmed Laminated Homogeneous λ No ND Iliuta IA [ 17 ] 2016 1 b Many segments Homogeneous λ PTC cytoplasm ND Kurien AA [ 18 ] 2018 1...…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, it has a lightly stained central area and a deeplystained burr-like edge, which is black, blue and fuchsia with PASM, Masson trichrome and PAS staining, respectively. Positive Congo red staining and electron microscopy can confirm its amyloid properties [ 15 , 16 , 18 , 19 ]. Under polarized light microscopy, ordinary light microscopy and fluorescence microscopy, Congo red staining exhibits apple green double refraction, brick red and bright red, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations